Dual-Gate Mosfet Static Characteristics Generated for Mixing Applications - Zimmermann, Detlef (My University, 1970)
The static electrical characteristics of dual-gate silicon n-channel insulated-gate field-effect trapsistors are investigated experimentally. A mathematical model based on theoretical expressions and containing twelve parameters adjusted for. best fit was developed.
The mathematical model was used to calculate the low frequency conversion transconductance as a function of operating conditions.
Keywords: mosfet; mixing application; electric; silicon